Workshop Pengelolaan dan Penyusunan RPS pada Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Trunojoyo Madura - Taembo, Maulid (Yayasan Arrahman Nahdlatul Wathan, 2024)
The lack of optimality in preparing the SLP (Semester Lesson Planning) and the existence of several SLP that had not been ratified were the reasons why this workshop activity was carried out. This workshop aims to resolve the issue of arranging and preparing SLP, producing SLP operational procedures, and guidelines for preparing SLP; and improving academic services, especially in the learning process. The activity began with reading the schedule of activities, praying, and providing direction from the study program coordinator as well as officially opening the event. The activity implementers collaborate and ask for guidance from experts in preparing operational procedures and guidelines for preparing the SLP. The workshop material includes the legal basis for preparing the SLP, the objectives of preparing the SLP and the definition, scope and provisions in preparing and managing the SLP. The activity closed by providing a conclusion and asking for the study program coordinator's willingness to close the activity and continued by giving the lecturer the opportunity to convey messages and impressions as a form of feedback on the activities that had been carried out. This workshop went well and received support from the participants, who took part in preparing the facilities and infrastructure used during the workshop, such as loudspeakers, tables, chairs and rooms. The participants were very happy with the existence of this workshop.